Prevalência do uso de medicamentos para transtornos psicossociais e do sono em mulheres climatéricas não usuárias de terapia de reposição hormonal - Costa, Camila Barbosa da (Universidade do Vale do Rio dos Sinos, 2014)
The growing need for rationalization of resources, especially with regard to developing countries, makes studies on drug use a device for cost reduction without loss of therapeutic quality, and may also present itself as a source of detection of abuse in use. medications or occurrence of adverse events. (MELO, RIBEIRO and STORPIRTIS, 2006). According to the literature on the use of medication, women are about twice as likely as men to have a prescription for medication, and this number increases when referring to psychotropic drugs. Middle-aged women are considered to be the group with the greatest use of these drugs, a characteristic that some researchers attribute to menopause.
Keywords: Uso de medicamentos; Transtornos psicossociais e do sono; Mulheres climatéricas; Terapia de reposição hormonal; Use of medications; Psychosocial and sleep disorders; Climacteric women; Hormone replacement therapy; ACCNPQ::Ciências da Saúde::Saúde Coletiva